NALAR ‘IRFANI: TRADISI PEMBENTUKAN DAN KARAKTERISTIKNYA - Nasrullah Nasrullah (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2013)
Leaning only to domination of the epistemology bayani and burhani is not enough. Both epistemology system must be completed with the epistemology of ’irfani which has a dimension of sprituality inmost. Logical reasoning system of the epistemology of ’irfani is a recontruction of the pure aspect of sprituality domain to get God’s knowledge and sense of humanity through authentic existential experinces